Pengembangan Model Komunikasi Organisasi Berbasis Nilai-Nilai Islam - Tyas Wiritanaya; Dhea Nabila Syahrani; Ismail Ahmad Mubarak; Lusiana Lusiana (Jurnal Multidisiplin Indonesia, 2023)
This research explores the characteristics of Islamic values-based organizational culture and the development of communication models that reflect Islamic principles. Islamic organizational culture reflects the implementation of Islamic teachings in organizational norms, behavior, and policies. These cultural characteristics, such as fairness, transparency, civility, honesty, and responsibility, are integrated into organizational communication models. This model of communication reinforces Islamic values, creating an ethical and harmonious working environment. Fairness in communication emphasizes equality and fairness, transparency promotes openness, politeness creates respectful relationships, honesty builds trust, and responsibility emphasizes organizational obligations. However, the development of this model is faced by challenges such as resistance to change, limited resources, and cultural diversity. Education, training, active participation, and external support can overcome these barriers. The challenges of intercultural communication are also addressed with strategies that consider cultural diversity. This research provides practical guidance for organizations that want to strengthen the Islamic dimension in their communication. With open dialogue, continuous evaluation, and attention to diversity, Islamic-based organizational communication models can be implemented effectively to achieve desired goals.